Anthropometric-Based Ergonomic Design of a Portable Mini Ladder Hoist for Loading and Unloading Operations at Medium-Scale Ports - Yohanes Viva Servianus; Gusti FX Wara Wangge; Matheus M Dwinanto; Fransiskus N Arfan (Universitas Mercu Buana, 2026)
Loading and unloading activities at small- and medium-scale ports are often performed manually, exposing workers to excessive physical loads, awkward postures, and an increased risk of work-related musculoskeletal disorders (WMSDs). This study aimed to develop an anthropometric-based ergonomic portable mini ladder hoist to improve the safety and efficiency of loading and unloading operations. The study employed a Research and Development (R&D) approach involving anthropometric measurements of 20 stevedores using 16 standing-posture dimensions. The collected data were analyzed using Minitab 19 to determine the mean, standard deviation, and 5th and 95th percentile values, which were used as the basis for ergonomic design. Morphological analysis and a weighted decision matrix were applied to generate and select the optimum design concept. The selected concept was modeled in SolidWorks and evaluated through engineering calculations, including structural strength, wire-rope selection, pulley sizing, and motor power requirements. The final design consisted of a portable wheel-mounted frame fabricated from S235 steel and powered by a 1 HP electric hoist. The ladder hoist was designed to safely support a total lifting load of 320 kg with a lifting height of 3 m. Ergonomic evaluation using the Rapid Entire Body Assessment (REBA) method indicated a reduction in risk level from high-risk manual handling to a medium-risk category after implementation of the proposed design. The novelty of this study lies in the integration of local port-worker anthropometric data, morphological design methods, and mechanical design considerations into the development of a portable ladder hoist. The proposed design provides a practical and cost-effective lifting solution for loading and unloading operations at medium-scale ports and similar material-handling environments.